An interpretation of spacecraft and ground based observations of multiple omega band events. (October 2015) - Weygand, J.M.; Kivelson, M.G.; Frey, H.U.; Rodriguez, J.V.; Angelopoulos, V.; Redmon, R.; Barker-Ream, J.; Grocott, A.; Amm, O.
Abstract: The source of the auroral phenomenon known as omega bands is not yet known. We examine in detail five different intervals when omega bands were observed on March 9th, 2008 between 0400 UT and 1100 UT over central Canada using both ground and space-based instrumentation. The THEMIS all sky imagers show the development of some of the omega bands from north–south streamers. Spherical elementary currents derived from ground magnetometer data indicate that the omega bands lie near the interface between the region 1 and region 2 currents in the post-midnight sector. THEMIS spacecraft data from the pre-midnight sector display multiple high speed flows and dipolarization features associated with high levels of geomagnetic activity, whereas four GOES geosynchronous spacecraft show multiple injections and dipolarization features. Magnetic field line tracing suggests that the magnetospheric location of the omega bands is at or just beyond geosynchronous orbit. We discuss in detail two potential source mechanisms for the omega bands: plasma sheet velocity shears and high speed flows in the magnetotail and relate the available data to those mechanisms. Our data and a magnetohydrodynamic (MHD) simulation support high speed flows in the magnetotail as the most likely generation mechanism, although the distribution of the magnetotail spacecraft does not provide unambiguous support for our interpretation of the source mechanism. Highlights: We examine ground and space based observations of 5 intervals of omega bands. We discuss in detail 2 potential source mechanisms for the omega bands. One mechanism we discuss is plasma sheet velocity shears. The other mechanism is high speed flows in the magnetotail. Our data and a MHD simulation support high speed flows as the likely mechanism.